Postpartum Mother Behavior 0-3 Days in Providing Colostrum in The working area of the Lubuk Tapi Health Center South Bengkulu Regency: Postpartum Mother Behavior 0-3 Days in Providing Colostrum in The working area of the Lubuk Tapi Health Center South Bengkulu Regency - Vevi Gusnidarsih (Institute Of Computer Science (IOCS), 2020)
To reduce the infant mortality rate and improve the health quality, it is Necessary to give good and Appropriate food for babies, one of the which is giving colostrum. The purpose of this research is to find out how the maternal attitudes by the postpartum of mother in colostrum are based on knowledge, attitudes, and actions. The method used in this research is a type of descriptive research method. The population of this research includes all the postpartum of mothers of 0-3 days that are in the working area of ??public health centers center in South Bengkulu Regency from September-November 2019 amounted to 36 postpartum of mother. The results of the study can be Noted that most of the respondents have knowledge about colostrum is less than 26 respondents (72.2%), respondents with a negative attitude of 21 respondents (58.33%),